DUKUNGAN KELUARGA DAN AKSESIBILITAS LAYANAN KESEHATAN TERHADAP KEPATUHAN PASIEN TB PARU DALAM MINUM OBAT - Abdullah, Asmiwarti; Djafar, Tanwir; Suyatni Musrah, Andi; Silfiana, Andi; Hermansyah, Hermansyah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Tuberculosis is currently still an infectious disease that has the most potential to endanger health. Based on the report of the Pekanbaru City Health Office in 2022, it is known that the highest tuberculosis cases occurred in the working area of the Sidomulyo RI Health Center, which amounted to 1446 cases. This study aims to determine the relationship of family support and accessibility of health services to adherence to taking medication. Quantitative research type with cross sectional design. The research was conducted in 2023 at Puskesmas RI Sidomulyo with a sample of 46 people. Data analysis was carried out univariate and bivariate. The research instrument used a research questionnaire. The results showed that there was a relationship between family support (p value = 0.016) and there was no relationship between accessibility of health services (p value = 0.402). It is recommended that the Puskesmas can provide education to pulmonary Tb patients by conducting regular counseling to patients both at the Puskesmas and home visits and providing training to doctors and nurses to be better trained in treating pulmonary Tb patients.Keywords: Family, Health Services, Tuberculosis